Pengaruh Board Size Terhadap Firm Value Melalui Earning Management Sebagai Variabel Intervening - Dikky Wijaya; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the direct and significant affect of board size to earning management,earning management to firm value, and board size to firm value. This study also examine the indirect and significant relationship of board size to firm value through earning management as intervening variable. The sample of this study was 34 companies listed in Indonesia Stock Exchange (IDX)This study used a quantitative approach, and the data were obtained from the company’s financial statement of 2011-2015. The data then processed by using smart PLS software. This study showed that there was negative and significant relationship of board size and earning management; negative and significant relationship of earning management and firm value; and positive and significant relationship of board size and firm value.